Antioxidant, antinociceptive, anti-inflammatory, and hepatoprotective activities of pentacyclic triterpenes isolated from Ziziphus oxyphylla Edgew. (4th July 2022) - , Abdullah; Khan, Mir Azam; Ahmad, Waqar; Ahmad, Manzoor; Adhikari, Achyut; Ibrar, Muhammad; Rehman, Maqsood ur; Asif, Muhammad
Abstract: Ziziphus oxyphylla Edgew is in folk use in Pakistan as an analgesic, anti-inflammatory, and liver ailments. Therefore, we have investigated antioxidant, antinociceptive, anti-inflammatory, and hepatoprotective activities of the isolated compounds (ceanothic acid and zizybrenalic acid) from the chloroform fraction of Z. oxyphylla . Ceanothic acid and zizybrenalic acid showed significant DPPH and H2 O2 scavenging activity as compared to control. In the acute toxicity study, ceanothic acid and zizybrenalic acid showed no toxic effects upto 200 mg/kg. The antinociceptive activity shown by ceanothic acid and zizybrenalic acid at 50 mg/kg was 64.28% and 65.35% compared to diclofenac sodium (72.3%) at 50 mg/kg. The percent inhibition of xylene-induced ear edema exhibited by ceanothic acid and zizybrenalic acid at 50 mg/kg was 51.33% and 58.66%, respectively, as compared to diclofenac sodium (72.66%). Both the isolated compounds exhibited inhibition of carrageenan-induced paw edema as compared to control. Hepatoprotection exhibited by zizybrenalic acid was more pronounced than ceanothic acid as observed from the decrease in carbon tetrachloride (CCl4 )-induced elevation of serum biomarkers, antioxidant enzymes and lipid peroxidation. Furthermore, zizybrenalic acid produced a marked decline in CCl4 -induced prolongation of phenobarbital-induced sleeping duration. Zizybrenalic acid exhibited 55.4 ± 1.37% inhibition of hypotonic solution-induced hemolysis compared to sodium salicylate (75.6 ± 2.15%). The histopathological damage caused by CCl4 was also countered by the administration of ceanothic acid and zizybrenalic acid. Ceanothic acid and zizybrenalic acid exhibited antioxidant, antinociceptive, anti-inflammatory, and hepatoprotective activities. Zizybrenalic acid exhibited better antioxidant, antinociceptive, anti-inflammatory, and hepatoprotective activity than ceanothic acid.